MLESET DALAM KARAWITAN: KASUS PADA GENDING PANGKUR - Hanggar Budi Prasetya; Adhi Susanto (Gelar : Jurnal Seni Budaya, 2010)
This article discusses rnleset phenomena in gamelan music. The main research question is why kenong and kempul instruments are played inmleset style. Acoustic and karawitanology approaches were used to analyze the problem. Two data type, qualitative and quantitative, were employed in this research. The recording of each gamelan pieces and the common gending (gamelan piece) constituted the quantitative data. These recordings were then analyzed through a computer  program, Wavelab 7. The qualitative data-experiences of the musicians were obtained through in-depth interview and observation done to the informants. The research revealed that rnleset is  classified as mleset nuntuni and mleset ngempyungi. Mlasat nuntuni is determined by the melody, while mleset ngempyungi is determined by patet(mode) and fundamental frequency of gamelan  instruments. Common instruments for plesetan are kenong and kempul, both with their unique sound frequency. Each of the instruments possesses fundamental frequency producing main  tone and overtone frequency, resulting in kernpyunq (kwint) orgembyang (octave) specific tone. The overtone frequency results in tonal interference which is culturally accepted as nice melody  by the listeners and the musicians.Key words: mleset, karawitan, gamelan, overtone